Legal Challenges in Protecting Minority Rights in a Plural Society - Nur Abdurakhman, Raden (Journal of Law and Social Politics, 2025)
Protecting minority rights presents significant legal challenges in plural societies due to sociopolitical, cultural, and institutional complexities. Despite international human rights frameworks advocating for inclusivity and equality, minority groups often face discrimination, marginalization, and legal barriers to accessing justice and equal opportunities. This study aims to analyze the legal obstacles hindering the protection of minority rights in plural societies and propose potential solutions within constitutional and human rights frameworks. Using a qualitative legal research method, this study employs a doctrinal approach by examining relevant legal instruments, court decisions, and academic literature. Additionally, comparative analysis assesses best practices from various jurisdictions to identify effective legal mechanisms for safeguarding minority rights. The findings indicate that key challenges include inconsistencies in national legislation, weak enforcement mechanisms, and the influence of majoritarian politics that often suppress minority rights. Furthermore, gaps in international legal frameworks and their implementation at the national level exacerbate these issues. The study highlights the importance of constitutional safeguards, judicial activism, and the role of civil society in strengthening legal protections for minorities. This research contributes to the discourse on legal pluralism and minority rights by offering policy recommendations to enhance legal frameworks to ensure non-discriminatory and equitable treatment of minority groups. It underscores the necessity of legal reforms, capacity-building for judicial and law enforcement institutions, and increased international cooperation to foster inclusive societies where minority rights are effectively protected.